Pengaruh Gaya Kepemimpinan Kepala Sekolah Terhadap Kinerja Belajar Siswa - Elli Widia; nanda harry mardika (Management Studies and Business journal, 2025)
This research explores the influence of the principal's leadership style on students' academic performance in schools. Unlike previous studies that often focus on teachers or administrative outcomes, this study specifically examines how different leadership styles of school principals affect student academic achievement. The study employed a quantitative approach with a correlational design, involving 80 students selected through total sampling. Data were gathered using validated and reliable instruments, including a leadership style questionnaire and academic performance records. Statistical analysis revealed that the principal’s leadership style has a significant effect on students’ academic performance. The findings confirm that Leadership Style contribute positively to Students' academic Performance, while authoritarian styles show a weaker correlation. These results highlight the importance of effective school leadership in fostering academic success and suggest that leadership development should be an integral part of educational management.